Métodos experimentais para determinação de propriedades do concreto baseados na mecânica da fratura - Paulo de Castro Guetti (2006)
Fracture Mechanics is a valuable tool towards the simulation concrete behavior, allowing a more realistic characterization of this material, in this way are now good reasons to believe that introduction of Fracture Mechanics into the design of concrete structures might be the next revolution. The main objective of this work is to appropriate and tospread out to structural engineering community new methodologies for the concrete characterization based on Fracture Mechanics concepts, mainly the experimental determination of the fracture energy, the most important fracture characteristic of the material, of different compressive strength concretes, made of routinely Brazilian concrete, cements and aggregates. Several beams have been tested to the determination of the fracture energy, for three categories of concrete strength that had been dosed to obtain the following characteristic strength values: 25 MPa, 40 MPa and 60 MPa. The specimens have notches at the middle sections and have been tested with concentrated loads at mid-span, simply supported at the ends (three-point bend beam test). Three draftRILEM recommendations had been implemented and tested. These recommendations are: 50-FMC, TC 89-FMT and the TC 89-FMT, that it considers the scale effect; and they are based in work developed by HILLERBORG (1986), JENQ and SHAH (1985) and BAZANT et al (1987), respectively. The test results are represented by the loaddisplacementcurves in the case 50-FMC, 89-FMT (based on size effect), while the other89-FMT results are represented by load-CMOD (crack mouth opening displacement) curve. The fracture energy values have presented different trends among the tested recommendations. The 50-FMC and the 89-FMT methods have shown the trend of increasing fracture energy so long as of the compressive strength increases and at the same time the concrete tends to become relatively more fragile. On the other side, the 89-FMT (based on size effect) method has shown decreasing fracture energy values with increasing compressive strength.